Differences between chronic and nonchronic depression: Systematic review and implications for treatment. Issue 1 (9th October 2018) - Köhler, Stephan; Chrysanthou, Sophia; Guhn, Anne; Sterzer, Philipp
Abstract : Background: There is still uncertainty if and to what extent chronic depression (CD) presents with specific features especially in contrast to the nonchronic course of major depressive disorder (non‐CD). This systematic review aims to summarize the existing literature regarding sociodemographic factors, psychopathology, and course of disease in patients with CD in comparison to patients with non‐CD. Methods: A structured database search (MEDLINE, PsycINFO, Web of Science, CENTRAL) was performed. All studies comparing CD with non‐CD patients were included. Twenty‐eight studies, including cohort studies, cross‐sectional studies, and observational studies, were identified in which both subgroups were diagnosed according to DSM‐IV or DSM‐5, respectively. Primary outcome were group comparisons focused on sociodemographic factors, childhood adversity, onset of the disorder, comorbidities, severity and course of the depressive symptoms, and specific psychopathology. Results: Patients with CD had an earlier onset of depressive symptoms, higher rates of psychiatric comorbidities, and a complicated treatment course (e.g., higher rates of suicidality) compared to non‐CD. We also found some evidence for specific features in the psychopathology of CD patients (submissive and hostile interpersonal styles) in contrast to non‐CD patients. Results were inconsistent with regard to childhood maltreatment. No differences were found regarding the severity of depressive symptoms and most sociodemographic factors. Conclusion: Despite some inconsistencies, the results of this review verified important differences between CD and non‐CD. However, future research is needed to characterize especially the specific psychopathology of CD in comparison to non‐CD patients to develop more tailored treatment strategies.